Study of the anticancer effect of new quinazolinone hydrazine derivatives as receptor tyrosine kinase inhibitors - Mortazavi, Motahareh; Divar, Masoumeh; Damghani, Tahereh; Moosavi, Fatemeh; Saso, Luciano; Pirhadi, Somayeh; Khoshneviszadeh, Mehdi; Edraki, Najmeh; Firuzi, Omidreza (Frontiers in Chemistry, 2022)
The advent of novel receptor tyrosine kinase inhibitors has provided an important therapeutic tool for cancer patients. In this study, a series of quinazolinone hydrazide triazole derivatives were designed and synthesized as novel MET (c-MET) receptor tyrosine kinase inhibitors. The antiproliferative effect of the synthesized compounds was examined against EBC-1, A549, HT-29 and U-87MG cells by MTT assay. MET kinase inhibitory effect was tested by a Homogenous Time Resolved Fluorescence (HTRF) assay. The antiproliferative effect of compounds in a three-dimensional spheroid culture was studied by acid phosphatase (APH) assay, while apoptosis induction was examined by Hoechst 33258 staining. We found that compound CM9 bearing p-bromo benzyl pendant inhibited MET kinase activity at the concentrations of 10–50 μM (% Inhibition = 37.1–66.3%). Compound CM9 showed antiproliferative effect against cancer cells, in particular lung cancer cells with MET amplification (EBC-1) with an IC50 value of 8.6 μM. Moreover, this derivative inhibited cell growth in spheroid cultures in a dose-dependent manner and induced apoptosis in cancer cells. Assessment of inhibitory effect of CM9 against a panel of 18 different protein kinases demonstrated that this compound also inhibits ALK, AXL, FGFR1, FLT1 (VEGFR1) and FLT4 (VEGFR3) more than 50% at 25 μM. Finally, molecular docking and dynamics simulation corroborated the experimental findings and showed critical structural features for the interactions between CM9 and target kinases. The findings of this study present quinazolinone hydrazide triazole derivatives as kinase inhibitors with considerable anticancer effects.